The impact of physical education classes on athletics selection for students in the second cycle of basic education (Comprehensive Journal of Science, 2026)
This study aimed to investigate the impact of the physical education (PE) lesson on the process of sports selection in athletics among students in the second cycle of basic education, through analysing the development of fundamental physical fitness components and identifying individual differences. The study adopted a descriptive analytical approach and involved a purposive sample of 80 students from Mousa Bin Nusayr Basic Education School during the 2025–2026 academic year. Data were collected using structured observation and standardized physical tests, including a 30m sprint, standing long jump, medicine ball throw, 800m run, and agility run, to measure speed, muscular strength, endurance, and coordination, The results revealed statistically significant differences between pre- and post-measurements at the 0.05 level across all tests, with t-values ranging from 6.58 to 8.12 and improvement percentages between 9.07% and 13.47%. The highest improvement was observed in upper-body muscular strength, followed by endurance. These findings confirm the effectiveness of scientifically planned PE lessons in developing fundamental physical abilities. Moreover, the study highlights the role of PE lessons in objectively identifying individual differences, thereby supporting sports selection processes in school athletics.
Keywords: Physical Education, Sports Selection, Athletics, Physical Fitness Components, Individual Differences, Basic Education